2016
DOI: 10.1002/1873-3468.12165
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray structure of linalool dehydratase/isomerase from Castellaniella defragrans reveals enzymatic alkene synthesis

Abstract: Edited by Stuart FergusonLinalool dehydratase/isomerase (Ldi), an enzyme of terpene degradation in Castellaniella defragrans, isomerizes the primary monoterpene alcohol geraniol into the tertiary alcohol (S)-linalool and dehydrates (S)-linalool to the alkene b-myrcene. Here we report on the crystal structures of Ldi with and without terpene substrates, revealing a cofactor-free homopentameric enzyme. The substrates were embedded inside a hydrophobic channel between two monomers of the (a,a) 6 barrel fold class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 38 publications
4
30
0
Order By: Relevance
“…a Active site of Elizabethkingia meningoseptica oleate hydratase (OhyA; PDB-code: 4UIR) with docked oleic acid in grey, FAD in yellow and catalytic residues in light orange (Engleder et al 2015). b Active site of Castelaniella defragrans linalool dehydratase-isomerase (LDI; PDB-code: 5HSS) with co-crystallised β - myrcene in orange and catalytic residues in magenta (Weidenweber et al 2016). c Active site of Pelobacter acetylenicus acetylene hydratase (ACH; PDB-code: 2E7Z) showing both MGD cofactors and the tightly coordinated tungsten (blue), as well as the [4Fe:4S] cluster and the catalytic aspartate (Seiffert et al 2007).…”
Section: Enzymes For Hydration and Their Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…a Active site of Elizabethkingia meningoseptica oleate hydratase (OhyA; PDB-code: 4UIR) with docked oleic acid in grey, FAD in yellow and catalytic residues in light orange (Engleder et al 2015). b Active site of Castelaniella defragrans linalool dehydratase-isomerase (LDI; PDB-code: 5HSS) with co-crystallised β - myrcene in orange and catalytic residues in magenta (Weidenweber et al 2016). c Active site of Pelobacter acetylenicus acetylene hydratase (ACH; PDB-code: 2E7Z) showing both MGD cofactors and the tightly coordinated tungsten (blue), as well as the [4Fe:4S] cluster and the catalytic aspartate (Seiffert et al 2007).…”
Section: Enzymes For Hydration and Their Propertiesmentioning
confidence: 99%
“…Since it is commercially hardly available, hydration of β-myrcene was suggested as an intriguing route for ( S )-(+)-linalool production (Lüddeke and Harder 2011; Demming et al 2018), even though its industrial application has not yet been reported. In contrast, LDI is already applied for the production of industrially highly relevant dienes such as isoprene and butadiene (Marliere 2013; Botes and Conradie 2015), which are amounting to market values of billions of dollars annually (Weidenweber et al 2016). …”
Section: Enzymes For Hydration and Their Propertiesmentioning
confidence: 99%
See 3 more Smart Citations